2015
DOI: 10.1093/mnras/stv553
|View full text |Cite
|
Sign up to set email alerts
|

On the possible environmental effect in distributing heavy elements beyond individual gaseous haloes

Abstract: We present a study of extended galaxy halo gas through H I and O VI absorption over two decades in projected distance at z ≈ 0.2. The study is based on a sample of 95 galaxies from a highly complete (> 80%) survey of faint galaxies (L > 0.1L * ) with archival quasar absorption spectra and 53 galaxies from the literature. A clear anti-correlation is found between H I (O VI) column density and virial radius normalized projected distance, d/R h . Strong H I (O VI) absorption systems with column densities greater … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

32
223
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 161 publications
(257 citation statements)
references
References 61 publications
32
223
1
Order By: Relevance
“…Liang & Chen (2014) have estimated this drop to be at d/Rvir ≈ 0.7 for Si II, Si III Si IV, C II and C IV. A similar drop of the C IV column densities was reported by Bordoloi et al (2014) at d/R200m ≈ 0.5, and for O VI by Johnson et al (2015) at d/Rvir ≈ 1.…”
Section: Comparison Of the Column Density Profiles In Simulations Andsupporting
confidence: 85%
See 2 more Smart Citations
“…Liang & Chen (2014) have estimated this drop to be at d/Rvir ≈ 0.7 for Si II, Si III Si IV, C II and C IV. A similar drop of the C IV column densities was reported by Bordoloi et al (2014) at d/R200m ≈ 0.5, and for O VI by Johnson et al (2015) at d/Rvir ≈ 1.…”
Section: Comparison Of the Column Density Profiles In Simulations Andsupporting
confidence: 85%
“…Some studies adopt rest frame equivalent width of W0 = 0.05 − 0.1Å and log N0 = 13.5 cm −2 as detection thresholds (Liang & Chen 2014;Johnson et al 2015). We adopt these values here for comparison with the derived covering fraction of data from Liang & Chen (2014) and Johnson et al (2015) for O VI. For observations where only equivalent width measurements are available, Liang & Chen (2014) adopted the threshold Wr = 0.05Å.…”
Section: Comparing the Cgm Covering Fractionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Kacprzak et al (2015) found that the equivalent width decreases as the distance of the absorber from the galaxy increases for the isolated sample. Similarly, Tumlinson et al (2011) and Johnson et al (2015) found that the column density decreases as the ratio of the impact parameter and the virial radius increases. We investigate this trend in group Prochaska et al (2011), (2) galaxies by showing the equivalent width as a function of the impact parameter in Figure 3.…”
Section: Modelingmentioning
confidence: 80%
“…This phenomenon suggests a deeper, underlying causal relationship between group galaxies and the larger dark matter halos in which they reside. While the question naturally arises whether environmental effects manifest in the CGM, research on the matter (Tejos et al 2012;Yoon & Putman 2013;Johnson et al 2014Johnson et al , 2015Wakker et al 2015;Finn et al 2016) is in its infancy.…”
Section: Introductionmentioning
confidence: 99%